Mobile business research : recent advances and future prospects - Giaglis, George M. (Business process management journal ;, 2006)
A great deal of attention has recently been paid to the potential of mobile communication technologies to redefine and extend the world of traditional eBusiness by rendering its applications available to mobile users. With mobile phone ownership outstripping the penetration of any other technology (computers, televisions, and the Internet alike) and no sign of reduction in demand for mobile online services, mobile business (mBusiness) is promising to permeate all areas of business and personal life with valuable and profitable applications and services in coming years. This special issue sets.